Restrictive trade practices and the European community (London : Federation of British Industries, 1966)
This text is a broad introduction to the Treaty's rules of competition and their complexities.
Loans
osa;23/07/17
Keywords: European Union; Restraint of trade; European Union; Restraint of trade -- Europe